Multimodality Assessment of Thoracic Aortic Dimensions: Comparison of Computed Tomography Angiography, Magnetic Resonance Imaging, and Echocardiography Measurements. Issue 6 (November 2020) - Frazao, Caio; Tavoosi, Anahita; Wintersperger, Bernd J.; Nguyen, Elsie T.; Wald, Rachel M.; Ouzounian, Maral; Hanneman, Kate
Abstract : Purpose: The purpose of this study was to compare thoracic aortic measurements between computed tomography (CT), magnetic resonance imaging (MRI), and transthoracic echocardiography (TTE). Materials and Methods: A total of 127 patients (mean age: 45±18 y, 49% male) who had undergone CT and MRI evaluation of the thoracic aorta at a single tertiary referral hospital within a 6-month interval between 2007 and 2017 were included in this retrospective study. TTE studies performed within the same 6-month interval were also evaluated. Thoracic aortic measurements were blindly evaluated using multiple techniques and were compared between modalities. Results: There was no significant difference in maximum aortic root diameter between CT and MRI when using the inner lumen-to-inner lumen technique (mean difference: 0.2±1.4 mm, P =0.51) or the outer lumen-to-outer lumen technique (mean difference: 0.5±1.4 mm, P =0.07). There were no significant differences between CT and MRI at any other level except for the distal descending aorta (20.2±4.6 vs. 19.8±4.6 mm, P <0.001). However, aortic root measurements by TTE using the leading edge-to-leading edge technique were significantly smaller compared with maximum aortic root diameters using the inner lumen-to-inner lumen and outer lumen-to-outer lumen techniques by both CT (mean difference: 4.9±2.7 mm, P <0.001 and 7.4±2.8 mm, P <0.001, respectively) and MRI (mean difference: 4.8±3.2 mm, P <0.001 and 8.2±3.0 mm, P <0.001, respectively). Conclusions: There is excellent agreement in thoracic aortic measurements between CT and MRI. However, TTE significantly underestimates maximum aortic root diameter compared with CT and MRI. Therefore, caution should be used when interpreting small apparent changes in aortic root diameters between TTE and CT or MRI.